Corylin from Psoralea fructus (Psoralea corylifolia L.) protects against UV‐induced skin aging by activating Nrf2 defense mechanisms. (12th July 2022) - Li, Nan; Liu, Tao; Zhu, Shan; Yang, Yi; Wang, Zijing; Zhao, Zhiyue; Liu, Tao; Wang, Xiang; Qin, Wenxiao; Yan, Yiqi; Liu, Yang; Xia, Qingmei; et al.
Abstract: Oxidative stress damage can lead to premature skin aging or age‐related skin disorders. Therefore, strategies to improve oxidative stress‐induced aging are needed to protect the skin and to treat skin diseases. This study aimed to determine whether the flavonoid corylin derived from Psoralea corylifolia can prevent UV‐induced skin aging and if so, to explore the potential molecular mechanisms. We found that corylin potently blocked UV‐induced skin photoaging in mice by reducing oxidative stress and increasing the nuclear expression of nuclear factor‐erythroid factor 2‐related factor 2 Nrf2. We also found that corylin stimulated Nrf2 translocation into the nucleus and increased the delivery of its target antioxidant genes together with Kelch‐like ECH‐associated protein 1 (Keap1) to dissociate Nrf2. These findings indicate that corylin could prevent skin aging by inhibiting oxidative stress via Keap1‐Nrf2 in mouse cells. Thus, Nrf2 activation might be a therapeutic target for preventing skin aging or skin diseases caused by aging. Our findings also provided evidence that warrants the further investigation of plant ingredients to facilitate the discovery of novel therapies targeting skin aging.